2008
DOI: 10.1051/0004-6361:20079288
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Martian water vapor over Hellas using OMEGA and PFS aboard Mars Express

Abstract: We used the OMEGA imaging spectrometer aboard Mars Express to study the evolution of the water vapor abundance over the Hellas basin, as a function of the seasonal cycle. The H 2 O column density is found to range from very low values (between southern fall and winter) up to more than 15 pr-µm during southern spring and summer. The general behavior is consistent with the expected seasonal cycle of water vapor on Mars, as previously observed by TES and modeled. In particular, the maximum water vapor content is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Few studies treated this effect in detail. We can refer to Encrenaz et al [5], which presented the results of the radiative transfer modelling of the same water band as observed by OMEGA. They found that the aerosol scattering lowers the 2.6 μm band depth by ∼ 2 − 8% for τ = 0.5 − 1.0 for a broad range of H 2 O mixing ratios.…”
Section: Uncertainties From the Climatological Modelmentioning
confidence: 99%
“…Few studies treated this effect in detail. We can refer to Encrenaz et al [5], which presented the results of the radiative transfer modelling of the same water band as observed by OMEGA. They found that the aerosol scattering lowers the 2.6 μm band depth by ∼ 2 − 8% for τ = 0.5 − 1.0 for a broad range of H 2 O mixing ratios.…”
Section: Uncertainties From the Climatological Modelmentioning
confidence: 99%
“…Since its first detection in the near infrared (Spinrad et al, 1963) water vapour in the Martian atmosphere has been extensively studied by ground-based and space borne observations (e.g. Sprague, et al 1996, Burgdorf, et al 2000, Gurwell, et al 2000, Smith 2002Biver, et al 2005, Fouchet, 2007, Encrenaz et al, 2008and Smith et al, 2009. Compared to water, there is only a sparse database for carbon monoxide at Mars.…”
Section: Introductionmentioning
confidence: 99%